Tingkat Literasi Financial Technology dan Kompetensi Akuntansi Pada Mahasiswa Akuntansi di Sumatera Selatan - Safitri, Rika Henda; Kalsum, Umi; HS, Rosihan Arief; Burhanuddin, Burhanuddin; Nurullah, Asfeni (E-Jurnal Akuntansi, 2023)
The research aims to prove the effect of financial technology literacy levels and accounting competence on accounting students in South Sumatra. The research sample consisted of 384 accounting students from public and private universities in the South Sumatra region. The data analysis technique uses multiple linear regression analysis. Based on the results of research using primary data in the form of questionnaires and the results of the analysis it is proven that there is an influence from financial literacy, financial technology, and accounting competence on student competence. Therefore, it can be said that one of the abilities that students need to have is financial literacy, in order to make it easier to make decisions about using finances. Keywords: Financial Literacy; Financial Technology; Accounting Understanding; student competencies